If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + x = 2x + 3 Reorder the terms: 10 + x = 3 + 2x Solving 10 + x = 3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 10 + x + -2x = 3 + 2x + -2x Combine like terms: x + -2x = -1x 10 + -1x = 3 + 2x + -2x Combine like terms: 2x + -2x = 0 10 + -1x = 3 + 0 10 + -1x = 3 Add '-10' to each side of the equation. 10 + -10 + -1x = 3 + -10 Combine like terms: 10 + -10 = 0 0 + -1x = 3 + -10 -1x = 3 + -10 Combine like terms: 3 + -10 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7
| y=-.7(30)+123 | | 5x+4y=38 | | 1/3(x+7)=5x-4(x-1)+19/3 | | x=3/4x+3 | | y=-.7(20)+123 | | a-3=5-a | | 3a*3a=6a | | x-5870.75=3520 | | y=-(1)+4 | | y=-(-0)+4 | | 1/4(x+3)=4x-3(1-x)-3 | | y=0.7(50)+123 | | y=-(-3)+4 | | F(0)=-3x+1 | | y=0.7(40)+123 | | y=-(-4)+4 | | 3/5(3x+4)=4(2-2x)+14 | | y=0.7(30)+123 | | g+4.6=19.3 | | F(-1)=-3+1 | | y*y+3y=0 | | x/-4+(-50)=-76 | | y=-0.7(20)+123 | | 25x^2-9=7 | | 6x-4=8-6x | | 2.5p=q+-1.6 | | -(x-4)=-22 | | y=5+4 | | 12c^2+8c+1=o | | y=4+4 | | y=3+4 | | -8+4y=4-6-3y-2 |